Petrilli, S., & Ji, M. (Eds.). (2022). Exploring the Translatability of Emotions: Cross-Cultural and Transdisciplinary Encounters. Palgrave Macmillan. https://doi.org/10.1007/978-3-030-91748-7 (pp.518) - Teng, Mei; Zhang, Xiaoyi (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2023)
Book review